Meningkatkan Kepuasan Kerja Melalui Kinerja dan Kesehatan Pegawai : Studi Empiris pada RSUD Arosuka - Afni Yeni; Ida Nirwana; Gita Marantika (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to explore the impact of work enhancement and employee benefits on job satisfaction among personnel at RSUD Arosuka. The concern arose from the hospital's choice to reduce the number of daily contract workers, leading to increased workloads and heightened job complexity. By employing a quantitative survey approach, this research collected data from a sample of 60 contract employees at RSUD Arosuka, selected using a Simple Random Sampling technique. The analysis utilized multiple linear regression, classical assumption tests (including normality, multicollinearity, autocorrelation, and heteroscedasticity), as well as hypothesis testing (t-test and F-test). The findings indicate that the Work Improvement variable (X1) does not significantly influence Job Satisfaction (Y) on an individual basis, as shown by a t-count value less than the t-table (0.509 < 1.672) and a significance value exceeding 0.05 (0.613 > 0.05). In contrast, the Employee Welfare variable (X2) reveals a significant individual effect on Job Satisfaction (Y), with a t-count value greater than the t-table (2.348 > 1.672) and a significance value lower than 0.05 (0.022 < 0.05). Nevertheless, when both Work Improvement (X1) and Employee Welfare (X2) are assessed together, they considerably affect Job Satisfaction (Y), as demonstrated by an F-count value exceeding the F-table (4.589 > 3.156) and a significance value below 0.05 (0.014 < 0.05).